2014
DOI: 10.3892/mco.2014.398
|View full text |Cite
|
Sign up to set email alerts
|

Time trends of clinical characteristics in hepatocellular carcinoma patients with chronic hepatitis B virus infection: A field survey between 2000 and 2012

Abstract: Abstract. The hepatitis B virus (HBV) carrier rate has decreased in Japan; however, the incidence of HBV infection among hepatocellular carcinoma (HCC) patients has not decreased accordingly. In this study, we aimed to assess the time trends of the clinical characteristics in HCC patients with chronic HBV infection. Between 2000 and 2012, we enrolled a total of 156 HCC patients with chronic HBV infection in our field survey. The HCC risk was evaluated using the HCC prediction score, which is constructed from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…On the other hand, HCC has become a common cause of admission in cirrhotic patients. Early detection by virtue of increased HCC surveillance 15 , 16 or an aging cohort of patients with HBV or HCV 15 , 17 could partly explain this finding.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HCC has become a common cause of admission in cirrhotic patients. Early detection by virtue of increased HCC surveillance 15 , 16 or an aging cohort of patients with HBV or HCV 15 , 17 could partly explain this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al found that DM is an independent risk factor for cirrhosis progression to HCC in patients with simple HBV infection [ 83 ], and Hsiang et al found that T2DM was predictor of liver-related complications and HCC in patients with HBV cirrhosis [ 84 ]. A Japanese study of 156 HCC patients with chronic HBV infection also suggested the involvement of T2DM in hepatocarcinogenesis in HBV-positive patients [ 85 ]. In 2012, a case-control study conducted in Taiwan concluded that synergistic interactions between T2DM and HBV infection increased the risk of HCC [ 86 ].…”
Section: Relationship Between Dm and Hcc With Different Etiologiesmentioning
confidence: 99%
“…[49] Supportingly, a study by Amano et al ., 2014 on HCC patients with HBV infection found T2DM to be significantly related to HCC in HBV patients. [50] Contradictorily, a cross-sectional study on cirrhotic patients with HBV with and without HCC found that diabetes was not a significant risk factor for HCC. [51] Similarly, Gao et al ., 2013 found that diabetes was analyzed to be independent of the prospect of HCC in cirrhotic patients with HBV infection.…”
Section: Introductionmentioning
confidence: 99%